2019
DOI: 10.1159/000500110
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise as Therapy for Type 2 Diabetes Mellitus: From Mechanism to Orientation

Abstract: Background: Exercise therapy plays an important role in the prevention and treatment of type 2 diabetes (T2DM). The mechanism of exercise therapy in the improvement of glycolipid metabolism of T2DM is very complex and not completely clear. Summary: Exercise training improves the whole body metabolic health in patients with T2DM, leading to an increase in glycolipid uptake and utilization, improved insulin sensitivity, optimized body mass index, and modulated DNA methylation, etc. Recent findings support that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 68 publications
4
63
0
7
Order By: Relevance
“…This gene has the responsibility in improving the skeletal muscle capability by increasing glucose uptake and transport .14 It also plays a role in body mass index (BMI) optimization, DNA methylation modulation, as well as upregulating some cytokines secretion that correlates with exercises and metabolic diseases. [15][16][17][18] The results of the current study are in line with the findings in a study performed by Paramitha 19 in 2014 where they showed a significant relationship between physical activity and blood glucose levels in DM-2 patients in Karanganyar District General Hospital, Surakarta with p = 0.001 and r =-0.433 and also a study by Nurayati and Adriani 20 in Surabaya city in 2007. Recently, DM-2 risk is increasing with a change in the lifestyle that adopts low activity level and high carbohydrate consumption.…”
Section: Discussionsupporting
confidence: 91%
“…This gene has the responsibility in improving the skeletal muscle capability by increasing glucose uptake and transport .14 It also plays a role in body mass index (BMI) optimization, DNA methylation modulation, as well as upregulating some cytokines secretion that correlates with exercises and metabolic diseases. [15][16][17][18] The results of the current study are in line with the findings in a study performed by Paramitha 19 in 2014 where they showed a significant relationship between physical activity and blood glucose levels in DM-2 patients in Karanganyar District General Hospital, Surakarta with p = 0.001 and r =-0.433 and also a study by Nurayati and Adriani 20 in Surabaya city in 2007. Recently, DM-2 risk is increasing with a change in the lifestyle that adopts low activity level and high carbohydrate consumption.…”
Section: Discussionsupporting
confidence: 91%
“…[67][68][69] PA plays a major role in the prevention and control of insulin resistance, prediabetes, GDM, T2DM, and diabetes related health complications. 70 Exercise is used for the prevention, 71 and treatment of T2DM [72][73][74][75][76][77][78] by improving glycemic control. 43,[79][80][81][82][83][84][85][86] It is a comprehensive element of diabetes management.…”
Section: Management Of T2dmmentioning
confidence: 99%
“…The mechanism of exercise in the improvement of T2DM is very complex and not completely known. 75 During an exercise, there is a complex biological response because almost all organs and systems are involved in the interactions that lead to adaptations at the levels of genetic, metabolic, and neuromuscular. 106 There are a few ways that PA could decrease BG levels.…”
Section: The Physiological Effects Of Physical Activity In T2dmmentioning
confidence: 99%
See 1 more Smart Citation
“…Das ultraschnelle Insulin aspart hat infolge rascherer Absorption eine doppelt so schnelle Anflutung im Blut und damit insbesondere in den ersten 30 Da sehr viele Menschen mit Typ-2-Diabetes neben der chronischen Hyperglykämie eine Vielzahl von weiteren vaskulären Risikofaktoren aufweisen, ist die Behandlung dieser Menschen komplex und soll alle vaskulären Risikofaktoren individuell berücksichtigen. Um dies deutlicher hervorzuheben, wurde der bisherige Therapiealgorithmus erweitert, um wesentliche kardiovaskuläre Risiken detaillierter zu adressieren (siehe dazu auch gesondertes Kapitel Lipidstoffwechselstörungen in diesen Praxisempfehlungen).…”
Section: Insulineunclassified